2019
DOI: 10.3329/jemc.v9i1.39902
|View full text |Cite
|
Sign up to set email alerts
|

Awareness Level of Cervical Cancer among Rural Women Attending Manikgonj 250-Bedded District Hospital, Manikgonj

Abstract: Background: Cervical cancer is a typically slow-growing cancer that may not have symptoms, but can be early diagnosed by Pap smear and Visual Inspection of Cervix with Acetic Acid (VIA). The burden of the disease is increasing in developing countries day by day due to the ascending trend of transmissible diseases such as HIV and Human Papilloma Virus (HPV). Objective: The main aim of this study was to assess the level of awareness regarding cervical cancer among the women attending outpatient department … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…The results revealed that 87% of participants knew about cervical cancer which is consistent with the study done in Bangladesh (Rahman and Bhattacharjee, 2019;Islam et al, 2015). This result is also similar to a study conducted in Northern India where 92% of participants heard of cervical cancer (10) and in Congo it is 82% which is close to our study (Ali-Risasi et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…The results revealed that 87% of participants knew about cervical cancer which is consistent with the study done in Bangladesh (Rahman and Bhattacharjee, 2019;Islam et al, 2015). This result is also similar to a study conducted in Northern India where 92% of participants heard of cervical cancer (10) and in Congo it is 82% which is close to our study (Ali-Risasi et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…and lack of knowledge of cervical cancer risk factors. 15,[18][19][20] Other risk Infection with HPV spreads from one individual to another through sex, including vaginal, anal, and oral sex. In a recent study, the prevalence of HPV in both urban and rural women in Bangladesh was reported to be 7.7%.…”
Section: Risk Factors Associated With Cervical Cancer In Bangladeshmentioning
confidence: 99%
“…Within Bangladeshi society, marriage at an early age and multiple births are very common. 15,20,[22][23][24] Cumulative evidence indicates that women who have their first full-term pregnancy at 17 years or younger are more likely to develop cervical cancer as compared with those who have their first full-time pregnancy at 25 years or older. 25 Women who have multiple full term pregnancies are more likely to be exposed to more frequent and unprotected intercourse, leading to higher chances of HPV infection.…”
Section: Risk Factors Associated With Cervical Cancer In Bangladeshmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the accessibility of effective screening strategies, there were wide disparities between countries regarding coverage of Cervical Cancer screening(CCS). For example, the magnitude of CCS was 80% in Austria [ 18 ], 29.55% in Bangladesh [ 19 ], 86.6% in South India [ 20 ], and 86.4% in Nepal [ 21 ]. Likewise, the magnitude of the CCS was 88.2% in Turkey [ 22 ], 94.1% in Kashmir [ 23 ], 28% in Uganda [ 16 ], and 36% in Kenya [ 24 ].…”
Section: Introductionmentioning
confidence: 99%